Ethanol pre-treatment to ultrasound-assisted convective drying of apple - Rojas, M. L. (2020)
For the first time, the ethanol as pre-treatment to the ultrasound-assisted convective drying of food was evaluated. Pre-treatments were performed by immersion of apple slices in ethanol (0-30 min). Pre-treated samples were convectively dried (50 degrees C, 1 m s(-1)), without/with ultrasound (21.77 kHz, 20.5 kW/m(3)). As results, if both technologies were considered, conventional drying time reduction reached 70 +/- 2%. From drying kinetics modelling, it was identified that ethanol pre-treatments mainly reduced the external resistance to mass transfer, while ultrasound had a greater influence on the internal one. In dried samples, as the ethanol pre-treatment time increased, the shrinkage decreased, and their rehydration capacity was greater. After rehydration, samples showed a decrease of> 85% in viscoelastic characteristics. The antioxidant capacity and total phenolic content were better retained with ultrasound application. The obtained results corroborate that the proposed technologies are complementary significantly accelerating the drying without negative effects on physical properties.